Interplay of DDP4 and IP-10 as a Potential Mechanism for Cell Recruitment to Tuberculosis Lesions - Blauenfeldt, Thomas; Petrone, Linda; del Nonno, Franca; Baiocchini, Andrea; Falasca, Laura; Chiacchio, Teresa; Bondet, Vincent; Vanini, Valentina; Palmieri, Fabrizio; Galluccio, Gianni; Casrouge, Armanda; Eugen-Olsen, Jesper; et al. (Frontiers in Immunology, 2018)
Introduction: Mycobacterium tuberculosis is one of the world’s most successful pathogens equipped to establish itself within the human host as a subclinical infection without overt disease. Unable to eradicate the bacteria, the immune system contains the infection in a granuloma structure. Th1 cells that are essential for infection control, are recruited to the site of infection directed by chemokines, predominantly CXCL10. It has previously been shown that CXCL10 in the plasma of patients chronically infected with hepatitis C virus is present primarily in an antagonist form. This is due to N-terminal truncation by the enzyme DPP4, which results in the antagonist form that is capable of binding its receptor CXCR3, but does not induce signaling. We aimed to explore whether such CXCL10 antagonism may have an impact on the pathogenesis of tuberculosis (TB). Results: We measured plasma levels of agonist and antagonist CXCL10 by Simoa digital ELISA, as well as DPP4 enzyme activity in the plasma of 20 patients with active TB infection, 10 patients with bacterial pneumonia infection and a group of 10 healthy controls. We found higher levels of total and antagonist CXCL10 and reduced DPP4 enzyme activity in the plasma of TB patients compared to controls. We traced the source of CXCL10 secretion using immunohistochemical and confocal analysis to multinucleated giant cells in the TB lesions, and variable expression by macrophages. Interestingly, these cells were associated with DPP4-positive T cells. Moreover, the analysis of lymphocytes at the site of TB infection (BAL), showed a reduced frequency of CXCR3+ T cells. Interpretation: Our data suggests that CXCL10 antagonism may be an important regulatory mechanism occurring at the site of TB pathology. CXCL10 can be inactivated shortly after secretion by membrane bound DPP4 (CD26), therefore reducing its chemotactic potential. Given the importance of Th1 cell functions and IFN-γ-mediated effects in TB, our data suggest a possible unappreciated regulatory role of DPP4 in TB. Perspectives DPP4 is the target for a class of enzyme inhibitors used in the treatment of diabetes, and the results from this study suggest that these drugs could be repurposed as an adjunct immunotherapy of patients.